Las Estrategias Metodológicas en el desarrollo del Pensamiento Lógico Matemático, en los niños de primero de básica de la Escuela de Educación Básica Fiscomisional “Fe y Alegría” de la ciudad de Riobamba, provincia de Chimborazo. Año Lectivo 2014 – 2015 - Alarcón Abarca, Paulina del Rocío (2016)
This research work is based on the problems examined in 5 year-old students of basic education at the "Fe y Alegría" school, who presented difficulties in the internalization of knowledge related to the mathematical logical thinking. The Inductive-deductive scientific methods were used; it is also a field research with a non-experimental design. The theoretical framework shows the research background and social, pedagogical, psycological, legal, and theoretical foundations, where strategies, methodologies, thinking, logic, mathematical intelligence, and the brain with its functions and hemispheres. The techniques and instruments for data collection were: the observation guide; and a survey with a questionnaire that were applied to children in order to obtain and organize information by using statiscal tables and charts, which serverd for the analysis and interpretation of data to test the hypothesis and finally the conclusions and recomendations in order to suggest a possible solution with a guide called "A guide for teaching assistance", which will benefit both teachers and students at the "Fe y Alegría" school.